Utilization of Entrepreneurial Skills and Economic Status Among Tesda Graduates - Faith O. Margate; Maya R. Sanchez (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study aimed to assess the utilization of entrepreneurial skills and the socioeconomic impact of the Technical Education and Skills Development training program in the province of Camiguin, the island born of fire in Northern Mindanao. Among the graduates of the training programs, 117 agreed to participate and provide the necessary information to answer the inquiries of this undertaking. Quantitative descriptive research design was employed with a survey questionnaire as the main data gathering tool, supplemented with a casual interview for clarification purposes. Research protocols were observed, and appropriate statistical tools were employed to produce reliable results. Analysis revealed that the counts of females were a little higher than their male counterparts. Most of the respondents belonged to the young adults, and the rest were middle-aged adults. The participants possessed diverse educational backgrounds and were employed in their respective localities after the training. The respondents exhibited a moderate utilization of entrepreneurial skills in terms of persistence, innovation, networking, and financial management skills. By sub-domain, however, the respondents need more training in financial management. Inferential analysis confirmed a highly significant difference in both employment type and personal income before and after the training program. These significant improvements indicate the program’s efficacy in impacting the socio-economic status of the TESDA graduates. Results also revealed no significant difference in the extent of utilization of entrepreneurial skills among the respondents when grouped by post-training income earned or by demographic variables like sex, age, educational attainment, and place of employment.